Biphasic effects of losartan potassium on immobility in mice - Vijayapandi, P.; Nagappa, A.N. (2005)
The effects of losartan potassium, an angiotensin AT, receptor blocker on immobility in forced swim test have been studied. Effect of losartan potassium, nortriptyline HCl, fluoxetine, HCl and reserpine per se and in combination on forced swimming-induced immobility in mice have also been studied. In mice, losartan potassium elicits biphasic responses i.e. positive responses at lower doses (0.1, 1.0 and 5 mg/kg, i.p.) in the forced swim test, a test of potential antidepressant activity and vice versa at higher dose (20 and 100 mg/kg, i.p.). In chronic studies, enhancement in immobility was observed for losartan potassium (3 and 30 mg/kg, p.o., 21 days). In acute combination studies, losartan potassium (1 and 5 mg/kg) significantly reversed the reserpine-induced immobility, but vice versa at 100 mg/kg. Losartan potassium (0.1 and 5 mg/kg) potentiate antidepressant activity of nortriptyline (30 mg/kg, i.p.) in mice, but vice versa at 100 mg/kg. Likewise, Losartan potassium (100 mg/kg), significantly reversed antidepressant activity of fluoxetine HCl, but at 0.1 and 5 mg/kg, failed to modify fluoxetine HCl induced immobility. The obtained biphasic effect of losartan potassium on immobility in mice might be due to inhibitory effect on AT(1) receptor at lower dose and pronounced effect on AT(2) receptor at higher dose (large concentrations of losartan potassium can displace Angiotensin II (Ang II) from its AT(1) receptor to AT(2) receptor.